A Supramolecular Crosslinker To Give Salt‐Resistant Polyion Complex Micelles and Improved MRI Contrast Agents. (29th August 2018) - Wang, Jiahua; Wang, Junyou; Ding, Peng; Zhou, Wenjuan; Li, Yuehua; Drechsler, Markus; Guo, Xuhong; Cohen Stuart, Martien A.
Abstract: Three‐component mixtures (diblock copolymer/metal ion/oligoligand) can assemble into micellar particles owing to a combination of supramolecular polymerization and electrostatic complex formation. Such particles cover a large range of compositions, but the electrostatic forces keeping them together make them rather susceptible to disintegration by added salt. Now it is shown how the salt stability can be tuned continuously by employing both a bis‐ligand and a tris‐ligand, and varying the ratio of these in the mixture. For magnetic ions such as Mn II and Fe III, the choice of the multiligand also affects the ion/water interaction and, hence, the magnetic relaxivity. As an example, Mn II ‐based nanoparticles with a very high longitudinal relaxivity (10.8 mm −1 s −1 ) were investigated that are not only biocompatible but also feature strong contrast enhancement in target organs (liver, kidney), as shown by T1 ‐weighted in vivo magnetic resonance imaging (MRI).